(3GSJjYGH GdhLhg GdeecfI aj UfYI GdGSWQdGHs - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO agPG cJGH eMeO Hf CMeO GdHjQhfi ai ESJjYGH GdhLhg GdeecfI ai UfYI GdCSWQdGH s
(3BNQgG (B:s
(3haYd Hg Pdc EMJed BaGb cKjQI hbGQHJ Cf JYe GdYQhV Cf TGA Gddg JYGdi Je cJGH GdGSJjYGH s
(3HgG CTcGd gfOSjIs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(46) s
Keywords: (3Gdadcs